Transformasi Pasar Modal Syariah Indonesia: Menavigasi Tantangan Digitalisasi dan Inklusi Keuangan di Era 5.0 - Maulana, Nora; Mukhtasar, Mukhtasar; Wibowo, Muhammad Ghafur; Razali, Razali; Safwan, Safwan (Jurnal Iqtisaduna, 2024)
The research aims to explore the development of the Indonesian Islamic capital market in the 5.0 era, explore the transformation, advantages and challenges faced by the Indonesian Islamic capital market, and formulate development strategies that can be applied in an effort to create a more modern, inclusive, transparent Islamic capital market structure, and still adhere to sharia principles. The research uses a qualitative method with an analytical literature approach. The findings of the research reveal that there are significant changes taking place in Indonesia's Islamic capital market. These transformations include the role of digitalization in promoting financial inclusion, the adoption of blockchain technology and digital security systems, the implementation of Islamic fintech, and the optimization of Islamic financial literacy. The research also highlights a series of strategic advantages for the development of Indonesia's Islamic capital market, including the synergy between the world's largest Muslim population and demographic bonus, increasing global demand for sustainable finance, and rapidly growing digital connectivity. The findings confirm a number of crucial challenges faced such as limited technological infrastructure, suboptimal regulatory harmonization, low levels of literacy, public perception and trust in Islamic capital markets, high competition with conventional capital markets, limited product variety, and risk management and security of digital transactions.